2021
DOI: 10.3389/fmicb.2021.614229
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Rhomboid-Like Protein 3 as a Candidate Antigen Against Eimeria maxima in Chickens

Abstract: Avian coccidiosis brings tremendous economic loss to the poultry industry worldwide. The third generation vaccine, including subunit and DNA vaccines, exhibited promising developmental prospects. In a previous study, we found rhomboid-like protein 3 of Eimeria maxima (EmROM3) was involved in infections by Eimeria species. However, the protective efficacy of EmROM3 against Eimeria maxima (E. maxima) remains unknown. In this study, chickens were intramuscularly immunized with the recombinant protein EmROM3 (rEmR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Our data supported the idea that NSLC protein as well as vaccines could generate an immune response, indicating that NSLC protein and vaccines possessed satisfactory immunogenicity. Similar to our results, immunity could be induced by the recombinant pET-32a-EmROM3 protein in chickens [52]. Furthermore, with the increased titres of IgY in immunized animals, our results also suggested that a booster immunity could be elicited by NSLC protein and vaccines.…”
Section: Immune Routesupporting
confidence: 90%
“…Our data supported the idea that NSLC protein as well as vaccines could generate an immune response, indicating that NSLC protein and vaccines possessed satisfactory immunogenicity. Similar to our results, immunity could be induced by the recombinant pET-32a-EmROM3 protein in chickens [52]. Furthermore, with the increased titres of IgY in immunized animals, our results also suggested that a booster immunity could be elicited by NSLC protein and vaccines.…”
Section: Immune Routesupporting
confidence: 90%
“…Serum levels of anti-EtROP17 antibodies were examined by ELISA as described elsewhere [ 8 ]. Briefly, the 96-well plate was coated with purified rEtROP17 and incubated overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Serum levels of anti-EtROP17 antibodies were examined by ELISA as described elsewhere [8]. Briefly, the 96-well plate was coated with purified rEtROP17 and incubated overnight at 4 • C. Following washing thrice with PBST, the plate was blocked with 5% skimmed milk in PBST.…”
Section: Determination Of Serum Antibody Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eukaryotic expression vector pVAX1 was purchased from Invitrogen (Carlsbad, California). Prokaryotic expression vector pET-28a, uninfected chicken serum, and chicken antiserum against E. maxima were preserved in our lab ( 10 , 11 ). Sporulated oocysts of E. maxima were stored in 2.5% potassium dichromate at 4°C.…”
Section: Methodsmentioning
confidence: 99%